Spanish language teaching in border contexts: the setbacks and the non-mandatory nature of its teaching in the new high school in the schools of Mâncio Lima/Acre - Dias, Jamile da Costa; Oliveira, Grassinete C. de Albuquerque (The ESPecialist, 2024)
This study presents an overview of Spanish language teaching in the city of Mâncio Lima - Acre. In this sense, the aim of this article is to investigate, from the field of Applied Linguistics, the teaching of Spanish in border contexts in the face of the setbacks imposed by the High School Reform (Law 13.415/2017), which establishes the non-mandatory teaching of Spanish in schools throughout Brazil. This study investigates the perceptions of three Spanish language teachers working in four state secondary schools in Mâncio Lima, which borders Peru. The methodology adopted was qualitative research with data collected using an online questionnaire (Google Forms), in order to understand, from the point of view of the Spanish language teachers in the primary school system in this municipality, the setbacks and implications of the trinational border (Acre - Peru - Bolivia) for the compulsory teaching of Spanish in schools in the state of Acre. The results show that the Spanish language continues to be taught on a compulsory basis in the city of Mâncio Lima, because it is located on the border with Peru and because it is a historically relevant language for the people of Acre.